Anther Culture In Rice: Progress And Breeding Perspective (Applied Biological Research, 2019)
Anther culture is an important biotechnological tool for the rapid recovery of  fixed breeding lines in rice. The method is largely species- and genotype specific. Indica rice is known to have a recalcitrant genetic background.  Oryza glaberrima responds better to the anther culture than O. sativa while japonica sub-group is more responsive to microspore embryogenesis than  Indica types. Media recipes and culture techniques have been standardized  for callus induction and green plantlet regeneration using Indica and  Japonica varieties as well as their inter se hybrids. Additive effects seem  more important than dominant effects of the genes concerned for callus  induction while preponderance of dominant effects is reported for  regeneration response. Sexual hybridization of rice sub-groups (Japonica x Indica) followed by the selection of favourable QTL for green plant  regeneration may be adopted to improve plant regeneration from anther derived callus in Indica rice. However, genetic transformation technology  using individual genes related to different aspects of anther culture could be  a more direct approach. This paper reviews the progress and breeding  perspective of anther culture in rice for genetic improvement of agronomic and stress-related traits using double haploid breeding.
Keywords: Anther cultur; double haploids; genetic improvement; rice